The crystal gryphon - Norton, Andre (New York : Atheneum, 1985)
Kerovan, whose cloven hoofs instead of feet set him apart from the human folk of the Dales, seeks to uncover the mystery surrounding his birth and the nature of his ultimate destiny
'A Margaret K. McElderry book.'
'First printing July 1972. Second printing June 1973'--T.p. verso of c. 2
Keywords: Witch World (Imaginary place); Fantasy fiction, American